Analysis of Differences Food Industry and Footwear Industry Sectors on Economic Growth of Industrial Sector in Mojokerto Regency - Yumna, Adinda; Sishadiyati, Sishadiyati (PT. Riset Press International, 2024)
The growth of the industrial sector has a significant impact on economic growth in a region. The industrial sector that dominates Mojokerto Regency is the food and footwear industry. Industrial development can be seen through the number of industries, workforce and investment. Even though they both dominate, the development of the footwear industry has decreased compared to the food industry which is increasingly developing well. The aim of this research is to determine the differences between the food and footwear industries and their influence on the economic growth of the industrial sector in Mojokerto Regency. This research is important because it not only discusses the differences between the food and footwear industries but also looks at the influence of these two industries on the economic growth of the industrial sector. This research uses a different test analysis method independent sample t-test and multiple linear regression analysis on time series data. The research results show that the number of industries and workers in the food and footwear industrial sector does not make a difference to the economic growth of the industrial sector, while investment in the food and footwear industrial sector has a difference to the economic growth of the industrial sector. Then the number of industries, workforce and investment in the food industry partially and simultaneously influence the economic growth of the industrial sector. While labor and investment in the footwear industry have an influence on economic growth, the number of industries in the footwear industry has no effect on the economic growth of the industrial sector in Mojokerto Regency.